Structural complexities and sodium-ion diffusion in the intercalates Na x TiS2: move it, change it, re-diffract it - Wiedemann, Dennis; Suard, Emmanuelle; Lerch, Martin (RSC advances, 2019)
After momentary attention as potential battery materials during the 1980s, sodium titanium disulphides, like the whole Na-Ti-S system, have only been investigated in a slapdash fashion. While they pop up in current reviews on the very subject time and again, little is known about their actual crystal-structural features and sodium-ion diffusion within them. Herein, we present a short summary of literature on the Na-Ti-S system, a new synthesis route to Na0.5TiS2-3R 1, and results of high-temperature X-ray and neutron diffractometry on this polytype, which is stable for medium sodium content. Based thereon, we propose a revision of the crystal structure reported in earlier literature (missed inversion symmetry). Analyses of framework topology, probability-density functions, and maps of the scattering-length density reconstructed using maximum-entropy methods (all derived from neutron diffraction) reveal a honeycomb-like conduction pattern with linear pathways between adjacent sodium positions; one-particle potentials indicate associated activation barriers of ca. 0.1 eV or less. These findings are complemented by elemental analyses and comments on the high-temperature polytype Na0.9TiS2-2H. Our study helps to get a grip on structural complexity in the intercalates Na x TiS2, caused by the interplay of layer stacking and Na-Ti-vacancy ordering, and provides first experimental results on pathways and barriers of sodium-ion migration.After momentary attention as potential battery materials during the 1980s, sodium titanium disulphides, like the whole Na-Ti-S system, have only been investigated in a slapdash fashion. While they pop up in current reviews on the very subject time and again, little is known about their actual crystal-structural features and sodium-ion diffusion within them. Herein, we present a short summary of literature on the Na-Ti-S system, a new synthesis route to Na0.5TiS2-3R 1, and results of high-temperature X-ray and neutron diffractometry on this polytype, which is stable for medium sodium content. Based thereon, we propose a revision of the crystal structure reported in earlier literature (missed inversion symmetry). Analyses of framework topology, probability-density functions, and maps of the scattering-length density reconstructed using maximum-entropy methods (all derived from neutron diffraction) reveal a honeycomb-like conduction pattern with linear pathways between adjacent sodium positions; one-particle potentials indicate associated activation barriers of ca. 0.1 eV or less. These findings are complemented by elemental analyses and comments on the high-temperature polytype Na0.9TiS2-2H. Our study helps to get a grip on structural complexity in the intercalates Na x TiS2, caused by the interplay of layer stacking and Na-Ti-vacancy ordering, and provides first experimental results on pathways and barriers of sodium-ion migration.